Line strength analysis of the second overtone 3ν2 band of D232S; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 270 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Belova A. S. Anastasiya Sergeevna; Morzhikova Yu. B. Yuliya Borisovna; Sydow C. Christian; Maul C. Christian; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann (2021, 2021)
Title screen